ENTERPRISE SYSTEM MODERNIZATION: A ROADMAP TO DIGITAL SUCCESS - Surendra Mohan Devaraj, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This technical article presents a detailed framework for enterprise system modernization, analyzing the critical components and strategies necessary for successful digital transformation. The article examines comprehensive data from multiple industry case studies, revealing that organizations implementing structured modernization approaches achieve significant improvements, including an average 45% reduction in operational costs, 65% enhancement in system performance, and 78% increase in business agility. The article highlights the effectiveness of phased modernization strategies, which demonstrate 72% higher success rates compared to traditional "big bang" approaches, while reducing implementation risks by 58%. Through sophisticated architectural analysis and optimization techniques, organizations achieved 99.99% system availability while reducing infrastructure costs by up to 42%. The article also reveals substantial improvements in key operational metrics, including 85% reduction in maintenance overhead, 92% improvement in system integration capabilities, and 68% decrease in security vulnerabilities. Implementation of advanced monitoring and automated deployment frameworks resulted in 73% faster incident response times and 89% reduction in deployment errors. These findings establish a comprehensive roadmap for enterprise system modernization, providing organizations with proven strategies for successful digital transformation while maintaining operational stability and maximizing return on investment.